EVALUATION OF COMPLIANCE WITH STANDARDS OF OPERATIONAL PROCEDURES FOR THE MEDICAL WASTE MANAGEMENT SYSTEM OF THE PUSKESMAS PANTE KUYUN, DISTRICT ACEH JAYA - Ichsan, Muhammad; Karma, Taufiq; Idroes, Ghazi Mauer (Transpublika Publisher, 2022)
The public health center in Pante Kuyun, situated in the Setia Bakti district of Aceh Jaya regency, Southeast Aceh, generates various types of medical waste during its operations. Improper management of medical waste can have negative impacts on both the environment and human health. This research aims to assess the current medical waste management practices at the Pante Kuyun public health center. The study utilized a descriptive observation method and revealed that the medical waste at the facility is not being handled in accordance with standard operating procedures. Waste segregation by type is lacking, and there is a lack of plastic bag liners and proper labeling for waste disposal. The findings of this study underscore the importance of implementing proper medical waste management practices at the Pante Kuyun public health center to protect both the environment and human health. Recommendations for improvement include providing staff with training on proper waste handling procedures, ensuring the availability of necessary resources for waste management, and implementing regular monitoring and evaluation of waste management practices at the facility.